A Chemically Defined Hydrogel for Human Liver Organoid Culture. (8th June 2020) - Ye, Shicheng; Boeter, Jochem W.B.; Mihajlovic, Marko; van Steenbeek, Frank G.; van Wolferen, Monique E.; Oosterhoff, Loes A.; Marsee, Ary; Caiazzo, Massimiliano; van der Laan, Luc J.W.; Penning, Louis C.; Vermonden, Tina; Spee, Bart; et al.
Abstract: End‐stage liver diseases are an increasing health burden, and liver transplantations are currently the only curative treatment option. Due to a lack of donor livers, alternative treatments are urgently needed. Human liver organoids are very promising for regenerative medicine; however, organoids are currently cultured in Matrigel, which is extracted from the extracellular matrix of the Engelbreth‐Holm‐Swarm mouse sarcoma. Matrigel is poorly defined, suffers from high batch‐to‐batch variability and is of xenogeneic origin, which limits the clinical application of organoids. Here, a novel hydrogel based on polyisocyanopeptides (PIC) and laminin‐111 is described for human liver organoid cultures. PIC is a synthetic polymer that can form a hydrogel with thermosensitive properties, making it easy to handle and very attractive for clinical applications. Organoids in an optimized PIC hydrogel proliferate at rates comparable to those observed with Matrigel; proliferation rates are stiffness‐dependent, with lower stiffnesses being optimal for organoid proliferation. Moreover, organoids can be efficiently differentiated toward a hepatocyte‐like phenotype with key liver functions. This proliferation and differentiation potential maintain over at least 14 passages. The results indicate that PIC is very promising for human liver organoid culture and has the potential to be used in a variety of clinical applications including cell therapy and tissue engineering. Abstract : Liver organoids are very promising for cell therapy and tissue engineering. However, organoids are cultured in Matrigel, which limits their clinical application. Here, a novel synthetic hydrogel for human liver organoid cultures is described. Organoids efficiently proliferate and differentiate in this polyisocyanopeptides (PIC)‐based hydrogel. As such, PIC is a promising material for human liver organoid culture and enables their clinical translation.